(untitled) - Sandler, Corey (Hoboken, N.J., 2015)
Samsung Galaxy Tab 4 NOOK For Dummies provides you with all the information you need to get the most out of your NOOK tablet. You'll quickly get up to speed on the basics, like using the touchscreen technology, setting up wireless access, and performing software updates. Then you'll get introduced to the fun stuff: downloading and shopping for e-books, using the built-in web browser, streaming videos from Netflix, Hulu, and other sources, and creating cool slideshows of photos from your digital camera. If that's not enough to pique your interest, you'll find out how to use the Android-based applications that come with the Samsung Galaxy Tab 4 NOOK, interact with the device using the built-in microphone, create your own e-books, archive your e-books, and so much more!
Keywords: Mobile computing,Samsung Galaxy Note (điện thoại thông minh),Điện thoại di động,Samsung Galaxy Note (Smartphone)